Experimental Characterization And Performance Analysis Of A Dual Axis Solar Tracking System Enhanced By Nano-Fluid Geothermal Cooling (International Journal of Environmental Sciences, 2025)
This study presents the experimental characterization and performance analysis of a dual-axis solar photovoltaic (PV) system integrated with a nano-fluid-based geothermal cooling mechanism. The system is designed to enhance PV module efficiency by maintaining optimal operating temperatures using a novel cooling loop consisting of iron oxide (Fe₃O₄) nano-particles dispersed in coconut oil as the working fluid. The dual-axis tracker maximizes solar energy capture by maintaining perpendicular alignment to the sun throughout the day, while the geothermal heat exchanger effectively dissipates excess heat absorbed by the PV panels. Experimental data were collected under varying environmental conditions, and key performance indicators such as electrical output, thermal behaviour, and efficiency were evaluated. The integration of tracking and hybrid cooling techniques demonstrates a promising approach for enhancing the performance of solar energy systems in high-temperature regions.The performance of the dual-axis tracked, nano-fluid cooled PV system was compared against both a conventional uncooled fixed-tilt PV system. Results show that the proposed setup yields a 12–17% improvement in electrical efficiency and a significant reduction in module operating temperature by up to 18°C compared to the reference systems. This hybrid approach-combining dual-axis tracking and nanofluid geothermal cooling-demonstrates a viable strategy for improving the performance and longevity of PV systems in hot climatic regions. The findings indicate the potential of nano-enhanced thermal management to play a critical role in the next generation of high-efficiency, sustainable solar technologies.